2016
DOI: 10.1097/dcr.0000000000000523
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Sacral Electrical Stimulation for Chronic Functional Constipation

Abstract: Continuous transcutaneous sacral stimulation in the short term appears to be ineffective for chronic constipation. Larger well-powered studies with intermittent stimulation regimens are required to investigate this further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…In 12 studies with 1805 patients, 14 , 16 , 17 , 21 , 22 , 24 - 26 , 31 , 33 , 34 , 36 pooled PAC-QOL was 1.97 (95% CI: 1.70-2.24) ( Figure 5 ). Publication bias was not evident (Egger P = .28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 12 studies with 1805 patients, 14 , 16 , 17 , 21 , 22 , 24 - 26 , 31 , 33 , 34 , 36 pooled PAC-QOL was 1.97 (95% CI: 1.70-2.24) ( Figure 5 ). Publication bias was not evident (Egger P = .28).…”
Section: Resultsmentioning
confidence: 99%
“…After screening 426 records for eligibility, 24 studies representing 3786 unique patients were included in the meta-analysis. 5 , 14 - 36 The most common reasons for study exclusion were attributable to absence of main outcome reporting or Rome III FC diagnosis. A flow diagram of study identification and selection is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The results of the 3 studies were in line with other studies despite including different population. [ 21 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…Clinical results are similar to gastric banding [ 96 ] Lower gastrointestinal tract dysfunctions include both hypomotility (constipation) and hypermotility (diarrhea and dumping syndromes). Digital stimulation of perianal cutaneous mechanoreceptors has long been used by paraplegic patients to stimulate fecal emptying, providing a basis for transcutaneous electrical stimulation [ 97 ]. Reduced intestinal motility has been noted in animal experiments on gastric stimulation, but clinical syndromes are mostly transient and/or respond well to drugs …”
Section: Case Studiesmentioning
confidence: 99%